Sociodemographic Differences in Pain Medication Usage and Healthcare Provider Utilization Among Adults With Chronic Low Back Pain - Allen-Watts, Kristen; Sims, Andrew M.; Buchanan, Taylor L.; DeJesus, Danica J. B.; Quinn, Tammie L.; Buford, Thomas W.; Goodin, Burel R.; Rumble, Deanna D. (Frontiers in Pain Research, 2022)
Chronic low back pain (cLBP) is the most common reason for individual suffering and health care utilization in adults. Ample evidence suggests sociodemographic variables and socioeconomic status (SES) influence pain. However, a framework informing associations on race, SES, and the utilization of pharmacologic therapies and provider type are limited—particularly in cLBP. Thus, this study examined the extent to which sociodemographic (i.e., age, race, and gender) and socioeconomic factors (i.e., national area deprivation index, NADI) influence pain treatment (i.e., NSAIDs, opioids, antidepressants, and non-NSAIDs) and provider utilization for cLBP (i.e., no provider care, primary care, or tertiary care). Eligible participants with cLBP completed a series of questionnaires. Of the 174 participants, 58% were women, 59% were non-Hispanic Black (NHB), and the mean age was 46.10 (SD 13.58). Based on NADI distributions by race, NHB participants lived in more socioeconomically disadvantaged neighborhoods (p < 0.001) than non-Hispanic White (NHW) adults. Results suggested that the use of one or more pharmacologic therapies was associated with race (p = 0.021). Specifically, NHW adults were two times more likely to take one or more pharmacologic therapies than NHBs (p = 0.009). NHWs were also more likely to use NSAIDs (p = 0.041) and antidepressants (p < 0.001) than NHBs. Furthermore, provider utilization was significantly associated with gender (p = 0.037) and age (p = 0.018); which suggests older women were more likely to use primary or tertiary care. Findings from this study expand on the existing literature as it relates to associations between disparities in access to healthcare providers and access to medications. Future research should seek to understand differences in age and utilization of primary or tertiary care providers and continue to examine the influence of sociodemographic and SES factors to cLBP and compare with other types of chronic pain.